Identification and characterization of leaf rust (Puccinia triticina) and Fusarium head blight (Fusarium graminearum) related genes in domesticated wheat varieties in Mongolia - Bold, Odgerel; Deriilaa, Otgon-Erdene; Baenziger, P.S. (Proceedings of the Mongolian Academy of Sciences, 2022)
Wheat is recognized as the major crop among all cereals. For better quality and disease-free production, the current study was designed to evaluate the prevalence of genetic leaf rust resistance and fusarium head blight in nineteen genotypes of wheat, which are commonly grown in Mongolia. For example Khalkhgol-1, Darkhan-131, Darkhan-160, Darkhan-144, Orkhon, Darkhan-34, Darkhan-74, Darkhan-193, Altaiskaya-100, Darkhan-181, Darkhan-141, Buryatskaya osistiya, Darkhan-166, Buryatskaya-79, Buryatskaya-34, Selenge, Altaiskaya-530, Altaiskaya-325 and Altaiskaya jinitsa genotypes. The presence of Lr34 and Fhbt1 genes were evaluated for leaf rust and fusarium head blight respectively. Lr34 gene was reported in the Darkhan-160 and Darkhan-181 genotypes, while fusarium head blight was not reported in any of the genotype.